A critical question: Can we trust smartphone survey data? - Tuncer, Murat (My University, 2017)
The main aim of this study is to determine whether a significant difference exits among data collection with printed materials and with smart phones. The research was conducted with 282 teacher candidates who take pedagogical formation training. Three data collection tools were used throughout the study. As the results of the current research, no significant differences were obtained among attitude scores towards teaching profession with regard to common effect of application method and faculty variables. However, significant differences in participant opinions were determined among different application methods (smartphone and printed) of Metacognitive Thinking Skills and Information Literacy Scales. In addition, no significant difference was found among opinions towards Metacognitive Thinking Skills and Information Literacy Scales with regard to common effect of application method and faculty variables. Based on these research findings, it is not recommended to distribute survey items containing technical information or some complex expressions via smartphones. Relations among the questionnaire content and the department of education confirm this situation.
Kritik bir soru: Akıllı telefon anket verilerine güvenebilir miyiz?
Makale - Yabancı Dilde Makale
Keywords: Smartphone; Online survey; Information Literacy; Metacognition Skills; Attitude towards teaching profession